Efficacy of cloth face mask in prevention of novel coronavirus infection transmission: A systematic review and meta-analysis - Suresh K Sharma; Mayank Mishra; Shiv K Mudgal (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Novel coronavirus is believed to be tiny enough (0.08-0.14 μm) to penetrate through face mask, thus protection offered by cloth mask may be too low. However, the use of cloth face mask in community has been recommended by the United States Centre for Disease Control and Prevention and regulatory bodies of other countries. There is paucity of literature on efficacy of cloth face mask in preventing SARS-CoV-2 infection transmission; thus, this review aims to update the available most recent evidences on efficacy of cloth face masks in prevention of viral infection transmission. METHODS: We searched MEDLINE, EMBASE, and Clinical Trials Register for identifying studies related to this review using free-text terms and MeSH terms. Both experimental and observational studies on efficacy of cloth masks which were published in English language have been included in this review except expert opinions, commentaries, editorials, and review articles. Twelve studies were eligible to be included in review for data extraction and qualitative synthesis was carried out from extracted data but quantitative analysis (meta-analysis) could not be performed because of serious heterogeneity between the studies. RESULTS: Cloth face masks show minimum efficacy in source control than the medical grade mask. The efficacy of cloth face masks filtration varies and depends on the type of material used, number of layers, and degree of moisture in mask and fitting of mask on face. CONCLUSION: Cloth face masks have limited efficacy in combating viral infection transmission. However, it may be used in closed, crowded indoor, and outdoor public spaces involving physical proximity to prevent spread of SARS-CoV-2 infection.